2022
DOI: 10.1371/journal.pone.0265686
|View full text |Cite
|
Sign up to set email alerts
|

Persisting olfactory dysfunction in post-COVID-19 is associated with gustatory impairment: Results from chemosensitive testing eight months after the acute infection

Abstract: Olfactory and gustatory disorders are prominent symptoms of acute COVID-19. Although both senses recover in many patients within weeks to months, persistency has been described in up to 60%. However up to now most reports on the course of chemosensitive disorders after COVID-19 are not based on psychophysical testing but only on subjective patients’ ratings. In this study we assessed both olfaction and gustation using psychophysical tests eight months after COVID-19. Validated psychophysical testing revealed h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 42 publications
0
13
0
1
Order By: Relevance
“…Since our study participants came for investigation after disease diagnosis at different time intervals, we expected their quantitative and qualitative characteristics would be different because of the time interval. We decided to conduct a study to evaluate neurosensory disturbances with respect to time because several studies observed that, if COVID-associated olfactory and gustatory disturbances were not improved within the first two weeks of recovery, they will persist for a long period [ 26 , 44 , 45 ]. Also, a scientific experiment found that the anatomical and functional recovery of the olfactory epithelium takes about 45 days [ 46 ] and odor perception takes about 90 days to recover [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since our study participants came for investigation after disease diagnosis at different time intervals, we expected their quantitative and qualitative characteristics would be different because of the time interval. We decided to conduct a study to evaluate neurosensory disturbances with respect to time because several studies observed that, if COVID-associated olfactory and gustatory disturbances were not improved within the first two weeks of recovery, they will persist for a long period [ 26 , 44 , 45 ]. Also, a scientific experiment found that the anatomical and functional recovery of the olfactory epithelium takes about 45 days [ 46 ] and odor perception takes about 90 days to recover [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Smell sensation is mainly perceived through two cranial nerves, that is, the olfactory and the trigeminal nerves [ 26 , 27 , 28 ]. It has been found that a majority of fragrances are recognized by both the nerves; however, there are a few orders specifically perceived by the olfactory or the trigeminal nerve [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemosensitive assessment is normally performed in specialized departments and comprises the collection of the patient's history, a clinical examination including nasal endoscopy and psychophysical testing. As SARS-CoV-2 positive patients are normally quarantined, home-based approaches have been established using self-prepared or shipped test kits combined with questionnaires [4,5], online surveys [6], or telephone interviews [7]. I.…”
Section: Dear Editormentioning
confidence: 99%
“…Por otro lado, según un estudio, aproximadamente el 25% de los pacientes estudiados presentaba deficiencias quimiosensoriales a los 8 meses, la cual se manifestaba con alteraciones gustativas y olfativas crónicas 14 .…”
Section: Introductionunclassified